Caspase 6 promotes innate immune activation by functional crosstalk between RIPK1-IκBα axis in liver inflammation - Yuanbang Lin; Mingwei Sheng; Hua Qin; Peng Zhang; Chunli Wang; Wei Fu; Xiangjun Meng; Duowei Wang; Yachao Hou (Cell Communication and Signaling, 2023)
Abstract Background Caspase 6 is an essential regulator in innate immunity, inflammasome activation and host defense. We aimed to characterize the causal mechanism of Caspase 6 in liver sterile inflammatory injury. Methods Human liver tissues were harvested from patients undergoing ischemia-related hepatectomy to evaluate Caspase 6 expression. Subsequently, we created Caspase 6-knockout (Caspase 6KO) mice to analyze roles and molecular mechanisms of macrophage Caspase 6 in murine models of liver ischemia/reperfusion (IR) injury. Results In human liver biopsies, Caspase 6 expression was positively correlated with more severe histopathological injury and higher serum ALT/AST level at one day postoperatively. Moreover, Caspase 6 was mainly elevated in macrophages but not hepatocytes in ischemic livers. Unlike in controls, the Caspase 6-deficient livers were protected against IR injury, as evidenced by inhibition of inflammation, oxidative stress and iron overload. Disruption of macrophage NF-κB essential modulator (NEMO) in Caspase 6-deficient livers deteriorated liver inflammation and ferroptosis. Mechanistically, Caspase 6 deficiency spurred NEMO-mediated IκBα phosphorylation in macrophage. Then phosphorylated-inhibitor of NF-κBα (p-IκBα) co-localized with receptor-interacting serine/ threonine-protein kinase 1 (RIPK1) in the cytoplasm to degradate RIPK1 under inflammatory conditions. The disruption of RIPK1-IκBα interaction preserved RIPK1 degradation, triggering downstream apoptosis signal-regulating kinase 1 (ASK1) phosphorylation and inciting NIMA-related kinase 7/NOD-like receptor family pyrin domain containing 3 (NEK7/NLRP3) activation in macrophages. Moreover, ablation of macrophage RIPK1 or ASK1 diminished NEK7/NLRP3-driven inflammatory response and dampened hepatocyte ferroptosis by reducing HMGB1 release from macrophages. Conclusions Our findings underscore a novel mechanism of Caspase 6 mediated RIPK1-IκBα interaction in regulating macrophage NEK7/NLRP3 function and hepatocytes ferroptosis, which provides therapeutic targets for clinical liver IR injury. Graphical Abstract Video Abstract